Dielectric Properties and Characterisation of Titanium Dioxide Obtained by Different Chemistry Methods - Wypych, Aleksandra; Bobowska, Izabela; Tracz, Milena; Opasińska, Agnieszka; Kadłubowski, Sławomir; Krzywania-Kaliszewska, Alicja; Grobelny, Jarosław; Wojciechowski, Piotr (Hindawi Publishing Corporation, 2014)
We made comparison of titanium dioxide powders obtained from three syntheses including sol-gel and precipitation methods as well as using layered (tetramethyl)ammonium titanate as a source of TiO2. The obtained precursors were subjected to step annealing at elevated temperatures to transform into rutile form. The transformation was determined by Raman measurements in each case. The resulting products were characterised using Raman spectroscopy and dynamic light scattering. The main goal of the studies performed was to compare the temperature of the transformation in three titania precursors obtained by different methods of soft chemistry routes and to evaluate dielectric properties of rutile products by means of broadband dielectric spectroscopy. Different factors affecting the electrical properties of calcinated products were discussed. It was found that sol-gel synthesis provided rutile form after annealing at 850°C with the smallest particles size about 20 nm, the highest value of dielectric permittivity equal to 63.7, and loss tangent equal to 0.051 at MHz frequencies. The other powders transformed to rutile at higher temperature, that is, 900°C, exhibit lower value of dielectric permittivity and had a higher value of particles size. The correlation between the anatase-rutile transformation temperature and the size of annealed particles was proposed.